Integrated treatment to resolve a horizontal root fracture - Brandini, Daniela Atili [UNESP]; Poi, Wilson Roberto [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Sonoda, Celso Koogi [UNESP]; Monteiro de Castro, Jose Carlos; Luvizuto, Eloa Rodrigues; Leal, Claudia Resende (Wiley-Blackwell Publishing, Inc, 2009)
Root fractures are defined as those that involve cement, dentin and pulp, comprising from 0.5 to 7% of injuries in permanent dentition. Diagnosis is made through clinical and radiographic exams, the latter frequently being limited by the position of the fracture. Treatment varies according to the displacement and vitality of the fragments. The authors present a clinical case of recurrent trauma of tooth 21 causing a horizontal root fracture in the middle third. After several attempts at endodontic treatment, the option was to remove the apical fragment by surgery. The postoperative period of 4 years shows very satisfactory results with regard to wound repair and tooth mobility, or implantation of the coronal segment.